Identification of potent chemotypes targeting Leishmania major using a high-throughput, low-stringency, computationally enhanced, small molecule screen. - Elizabeth R Sharlow; David Close; Tongying Shun; Stephanie Leimgruber; Robyn Reed; Gabriela Mustata; Peter Wipf; Jacob Johnson; Michael O'Neil; Max Grögl; Alan J Magill; John S Lazo (Public Library of Science (PLoS), 2009)
Patients with clinical manifestations of leishmaniasis, including cutaneous leishmaniasis, have limited treatment options, and existing therapies frequently have significant untoward liabilities. Rapid expansion in the diversity of available cutaneous leishmanicidal chemotypes is the initial step in finding alternative efficacious treatments. To this end, we combined a low-stringency Leishmania major promastigote growth inhibition assay with a structural computational filtering algorithm. After a rigorous assay validation process, we interrogated approximately 200,000 unique compounds for L. major promastigote growth inhibition. Using iterative computational filtering of the compounds exhibiting > 50% inhibition, we identified 553 structural clusters and 640 compound singletons. Secondary confirmation assays yielded 93 compounds with EC(50)s < or = 1 microM, with none of the identified chemotypes being structurally similar to known leishmanicidals and most having favorable in silico predicted bioavailability characteristics. The leishmanicidal activity of a representative subset of 15 chemotypes was confirmed in two independent assay formats, and L. major parasite specificity was demonstrated by assaying against a panel of human cell lines. Thirteen chemotypes inhibited the growth of a L. major axenic amastigote-like population. Murine in vivo efficacy studies using one of the new chemotypes document inhibition of footpad lesion development. These results authenticate that low stringency, large-scale compound screening combined with computational structure filtering can rapidly expand the chemotypes targeting in vitro and in vivo Leishmania growth and viability.